2020
DOI: 10.1007/s10639-020-10380-4
|View full text |Cite
|
Sign up to set email alerts
|

Are teachers techno-optimists or techno-pessimists? A pilot comparative among teachers in Bolivia, Brazil, the Dominican Republic, Ecuador, Finland, Poland, Turkey, and Uruguay

Abstract: The aim of the article is to highlight the key elements related to the implementation of new technologies in education from the perspective of the opinions and experiences of educators in the field in Bolivia, Brazil, the Dominican Republic, Ecuador, Finland, Poland, Turkey, and Uruguay. The text compares issues related to attitudes towards the use of new media in education, experiences with different forms of e-learning, and the level of restrictions on the use of smartphones in school. These variables are ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 32 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…Even if teachers are skilled enough in technology and first-order barriers are resolved, they cannot still apply appropriate ICTs in their teaching due to the internal barriers, such as their views and attitudes towards ICTs in education based on their pedagogical beliefs (Fokides & Kostas, 2020 ). In this context, Tomczyk et al ( 2020 ) identified four categories of teachers’ attitudes towards new media: techno-optimist, techno-realist, techno-pessimist, and techno-ignorant. Techno-optimist teachers are enthusiastic and realize that new media could positively affect the quality and effectiveness of education.…”
Section: Introductionmentioning
confidence: 99%
“…Even if teachers are skilled enough in technology and first-order barriers are resolved, they cannot still apply appropriate ICTs in their teaching due to the internal barriers, such as their views and attitudes towards ICTs in education based on their pedagogical beliefs (Fokides & Kostas, 2020 ). In this context, Tomczyk et al ( 2020 ) identified four categories of teachers’ attitudes towards new media: techno-optimist, techno-realist, techno-pessimist, and techno-ignorant. Techno-optimist teachers are enthusiastic and realize that new media could positively affect the quality and effectiveness of education.…”
Section: Introductionmentioning
confidence: 99%
“…10). The majority of employers (26%) focused on a fear of new trends and technopessimism (Tomczyk et al, 2020) as the main barrier. They mentioned "a lack of confidence in their own digital abilities", the fact that "teachers are convinced that it is possible to teach effectively in the old way", "the teaching staff are committed to the traditional teaching tools" and "they seem unable to adapt flexibly to new conditions".…”
Section: Barriersmentioning
confidence: 99%
“…Before COVID-19, digital technologies found their way into educational practices in varying degrees but were not fully integrated (Tomczyk et al, 2020). The COVID-19 pandemic, however, has accelerated the integration process and given a spur to global discussions of the consequences of the shift towards digitalization (Rajab et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2020), however there are not many studies examining how to induce educators to change attitudes towards the use of ICT, in terms of understanding its true added value in teaching itself from a didactic point of view and increasing their motivation to use ICT in teaching. For example, Tomczyk et al (2020a) concluded based on research that teachers tend to be more of "techno-optimists". Hanafi et al (2017) addressed the reasons for the low motivation of university students to participate in the ICT use course in teaching (e.g., due to a lack of experience in ICT).…”
Section: Introductionmentioning
confidence: 99%